ANALISIS TRANSPORTASI DALAM SISTEM LOGISTIK PADA PERUSAHAAN EKSPEDISI - Almeira Zahrah Kusriana; Keisya Rifael (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Transportation is a fundamental component of the logistics system, serving as the link between production, distribution, and consumption activities. Freight forwarding companies are required to provide delivery services that are fast, timely, secure, and efficient to meet the continuously evolving needs of customers. This study aims to analyze the role of transportation in the logistics systems of freight forwarding companies through a literature review approach. The research employs a descriptive qualitative literature review by examining books, scientific journals, and relevant reports related to transportation, logistics, and supply chain management. The findings indicate that the effectiveness of logistics systems is influenced by transportation mode selection, distribution route optimization, the utilization of information technology, the quality of human resources, and transportation cost management. Freight forwarding companies also face several operational challenges, including traffic congestion, rising fuel prices, inadequate infrastructure, and increasing customer expectations for faster delivery services. Therefore, companies need to optimize their transportation systems through digitalization, technology integration, and effective distribution strategies to enhance operational efficiency and maintain competitive advantage.